Analytical studies on the (1+1)-dimensional nonlinear Dispersive Modified Benjamin-Bona-Mahony equation defined by seismic sea waves - Baskonus, Haci Mehmet; Bulut, Hasan (Taylor & Francis Ltd, 2015)
In this study, we have studied to obtain some new analytical solutions to the (1+1)-dimensional nonlinear Dispersive Modified Benjamin-Bona-Mahony equation by using modified exp-function method. We have submitted the general structure of modified exp-function method. We have founded some new analytical solutions such as hyperbolic and rational function solutions. Afterward, we have plotted 2D and 3D surfaces of analytical solutions obtained in this study by using computer programming wolfram Mathematica 9.
Keywords: Exp-Function Method; Evolution-Equations; Asymptotic Methods; Periodic-Solutions